Specific enzyme activities of trypsin and chymotrypsin in various age of Tilapia, Oreochromis niloticus, tested at different temperatures - Vuthiphandchai, Verapong; Hopradermnusorn, Sirinard; Sooksawat, Treerat; Nimrat, Subuntith (Science Essence Journal, 2020)
The objectives of this study were to evaluate the effects of age of tilapia (Oreochromis niloticus) and tested temperatures on in vitro enzymes activities of trypsin and chymotrypsin. Extracted enzymes from the intestine of tilapia age 45-140 days were determined specific enzyme activities of trypsin and chymotrypsin at various temperatures between 30-70 ºC and 20-60 ºC, respectively. Expression of specific activities of trypsin (T) and chymotrypsin (C) depended on fish age and tested temperatures. The highest specific activity of trypsin was found in fish aged 105 days using a tested temperature of 70 ºC whereas that of chymotrypsin was observed at fish aged 120 days using 60 ºC. Tested temperatures resulting in the highest specific activities of trypsin and chymotrypsin were detected at 70 ºC and 60 ºC, respectively. The T/C ratio in fish aged 105 days had the highest value, compared to those of other fish age. An increase in tested temperatures resulted in higher T/C ratio. This study allowed understanding of the expression of specific activities of trypsin and chymotrypsin of tilapia at various age, which can be used as the baseline information for further development of suitable feed formulation of tilapia based on in vitro digestibility.